2021
DOI: 10.1097/meg.0000000000002070
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing health-related quality of life in patients with Barrett’s esophagus: a qualitative focus group study

Abstract: Introduction Barrett's esophagus is a premalignant condition in the lower part of the esophagus, caused by gastroesophageal reflux disease. Previous studies found that having a Barrett's esophagus is associated with a significant decrease of health-related quality of life (HRQOL). Over the past decade, a considerable amount of literature has been published on the development of endoscopic treatment for (early) neoplasia in Barrett's esophagus. Though, currently very little is known about the impact of those en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“… 18 This finding suggests a minimal influence on generic HRQoL by the diagnosis of BE. This coincides with our earlier observations in focus‐groups interviews 32 and a single center questionnaire study, 6 which showed Dutch BE patients experience a good HRQoL. Nevertheless, this finding contradicts previous studies, which have concluded that patients with BE reported decreased HRQol on the SF‐36, compared to norm reference data.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“… 18 This finding suggests a minimal influence on generic HRQoL by the diagnosis of BE. This coincides with our earlier observations in focus‐groups interviews 32 and a single center questionnaire study, 6 which showed Dutch BE patients experience a good HRQoL. Nevertheless, this finding contradicts previous studies, which have concluded that patients with BE reported decreased HRQol on the SF‐36, compared to norm reference data.…”
Section: Discussionsupporting
confidence: 88%
“…18 This finding suggests a minimal influence on generic HRQoL by the diagnosis of BE. This coincides with our earlier observations in focus-groups interviews 32 and a single center questionnaire study, 6 contradicts previous studies, which have concluded that patients with BE reported decreased HRQol on the SF-36, compared to norm reference data. A more recent study in the UK showed NDBE patients had significantly lower scores across all domains of the SF-36 compared to a healthy cohort.…”
Section: F I G U R Esupporting
confidence: 86%
See 2 more Smart Citations
“…Four studies with a qualitative design were identified: one study used a focus group design and three used patient interviews [43][44][45][46]. The study characteristics and quality scores are demonstrated in Table 3.…”
Section: Identification Of Influencing Factors According To Be Patientsmentioning
confidence: 99%